Heart rate variability is associated with thermal heat pain threshold in males, but not females - Tracy, Lincoln M.; Koenig, Julian (International journal of psychophysiology, 2018)
Previous research has suggested that heart rate variability (HRV; the variability in the interval between successive heartbeats) can predict the perception of experimentally-induced pain (i.e., pain sensitivity). However, little research has sought to investigate sex-specific associations between HRV and pain sensitivity. This is an important consideration, given that sex differences in resting HRV have been observed, and there has been extensive debate about sex differences in sensitivity to experimentally-induced pain. We examined whether the association between resting HRV and sensitivity to experimentally-induced pain differed in men and women. Fifty-one pain free individuals (26 women, mean age=21.9years) participated. Resting electrocardiography (ECG) was collected during a paced breathing task (15cycles per minute), and measures of HRV were extracted via Fast Fourier Transformation. Thermal heat pain threshold (i.e., the point at which the sensation was first perceived as painful, rather than warm) was measured with a Medoc Pathway Pain and Sensory Evaluation System. There were no sex differences in resting HRV or thermal heat pain threshold, nor did sex moderate the relationship between HRV and thermal heat pain threshold. However, there were significant positive relationships between thermal heat pain threshold and LF-HRV (r=0.47), and HF-HRV (r=0.43) in men, but not in women. The results suggest that higher pain threshold appears to be related to greater engagement of the inhibitory parasympathetic nervous system in men only, and that other biopsychosocial mechanisms may contribute to experimental pain experience in women. Future research is needed to study these mechanisms further, accounting for other factors known to influence nociceptive and cardiovascular regulatory processes (e.g., ethnicity, hormones).
Gesehen am 03.05.2019